Transcriptional and physiological analyses uncover the mineralization and uptake mechanisms of phytic acid in symbiotically grown Vicia faba plants - Amoako, Frank K (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 The Authors. Published by Elsevier Masson SAS.. All rights reserved.